Learning in Clinical Research: Hybrid Teaching Experience with Medical Students - Grande Ratti, María F.; Kiblisky Elizalde, Valentina; Burgos, Mariana A.; Russo, María P.; Martínez, Bernardo J. (Revista del Hospital Italiano de Buenos Aires, 2023)
Introduction: The COVID-19 pandemic induced a change in our health and education system. Training programs also had to adapt into a rapid change.Objectives: To describe an educational experience of virtual teaching in clinical research, between medical students of the Instituto Universitario del Hospital Italiano and teachers of the Clinical Service of the Hospital Italiano de Buenos Aires, who participated in the ESIN Program.Methodology: The educational program comprised various contents and instructional approaches, including asynchronous and self-administered audio or video-recorded theoretical classes, project-based learning, practical workshops conducted through virtual group synchronous meetings, and the implementation of the inverted classroom model. Additionally, individual tutoring sessions were provided between teachers and students. Data collection involved observing academic contexts and gathering feedback through anonymous satisfaction surveys, with participants providing prior informed consent.Results: Fourteen students participated, 6 during 2021 and 8 during 2022. All female, and medical students (50% fourth year, 35% sixth year and 15% fifth year). The techniques implemented favored participation and promoted active, project-based learning. They mentioned positive aspects such as the practical academic approach, the availability of the teaching team for any doubts, the time and enthusiasm for teaching and encouraging participation. The theoretical videos were useful as review tools, and the group meetings were especially valued, although the individual meetings were highlighted as help and support prior to the scientific congresses. In general, they stated that it was an enriching experience that showed that it is possible to achieve what was thought to be impossible. All of them actively participated in at least one scientific congress, and 50% were co-authors of an academic publication.Conclusion: Throughout the educational program, students embraced commitments and responsibilities while acquiring valuable competencies and skills in project implementation and dissemination. This approach effectively optimized class time, fostering fruitful exchanges, discussions, and opportunities for addressing any doubts. All the resources produced, activities developed, and content covered during the program are readily accessible at the institutional level.<
Keywords: education; medical; undergraduate; research personnel; problem-based learning; information science; congresses as topic; peer review; research